Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Photoactive anthraquinone-based host-guest assembly for long-lived charge separation - Jha, Ajay; Mote, Kaustubh R.; Chandra, Suman; Madhu, Perunthiruthy K.; Dasgupta, Jyotishman (Journal of Physical Chemistry C, 2021)
Porous 2D covalent organic frameworks (COF) that are assembled axially through weak p-stacking interactions can provide reticular charge transport channels while playing host to kinetically stabilized reactive molecular redox states. Here we demonstrate a host-guest supramolecular charge transfer (CT) assembly using photoactive anthraquinone-based COF as an acceptor while incarcerating the electron donor N,N-dimethylaniline (DMA) inside it. Employing femtosecond broadband transient absorption spectroscopy in combination with electron paramagnetic resonance (EPR) studies, we show that the CT occurs rapidly within <110 fs after photoexcitation, subsequently leading to long-lived charge separation with 13% quantum efficiency at room temperature. The photoinduced EPR signature of the long-lived confined DMA cation radical confirms the disparate regions of charge localization while H-1-C-13 correlation experiments using solid-state NMR spectroscopy enumerate the packing of the amines inside the host-guest COF assembly. Our work demonstrates the potency of charge transport pathways in supramolecular assemblies for efficient charge separation which if optimally tuned should pave the way for COF-based photocatalytic reaction centers.